ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 56/PUU-XX/2022 TENTANG PENGUJIAN MATERIIL PASAL 27 A AYAT (2) HURUF B UNDANG-UNDANG NOMOR 7 TAHUN 2020 TENTANG MAHKAMAH KONSTITUSI - Samuel Yakub Radja Gnting Suka; Mexsasai Indra; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Judicial power is an independent and independent power that carriesout a judicial function in the field of justice. The Constitutional Court is a stateinstitution that carries out the functions of judicial power which is grantedconstitutional authority in Article 24 letter C of the 1945 Constitution of theRepublic of Indonesia. In addition, the Judicial Commision is part of the judicialpower but does not carry out a judicial function. Judicial Commision is only aninstitution that balances the power of the judiciary which has the authority by theConstitution to maintain and uphold the nobility and behavior of judges.The type of research used by the author is normative legal research orwhat is known as